Optimizing Energy Alternatives in Colombia’s Isolated Regions: A Multi-Criteria Evaluation - Díaz Tapia, Luis Daniel; Manyoma Velásquez, Pablo César; Manotas Duque, Diego Fernando (International Journal of Energy Economics and Policy, 2025)
Access to affordable, reliable, and sustainable energy is crucial for achieving the Sustainable Development Goals, improving quality of life, combating poverty, and fostering socioeconomic growth. However, a significant portion of the global population still struggles with energy poverty, lacking access to basic services such as electricity and clean cooking. Current strategies to combat this issue often rely on fossil fuels, which are costly and have negative environmental and health impacts. Hybrid energy systems offer a promising solution, but designing and evaluating them is complex. This study proposes an integrated approach for tackling that problem using Hybrid Optimization of Multiple Energy Resources (HOMER) software, along with the Criteria Importance Through Inter-Criteria Correlation (CRITIC) and multi-criteria decision making method (VIKOR). The methodology was applied to a case study in a remote region of Colombia. Results demonstrate that this approach enhances decision-making and identifies viable alternatives for energy-poor regions, providing a valuable tool for energy planning in developing contexts.